Early to mid Wisconsin Fluvial Deposits and Palaeoenvironment of the Kidluit Formation, Tuktoyaktuk Coastlands, Western Arctic Canada. (25th April 2017) - Murton, Julian B.; Bateman, Mark D.; Telka, Alice M.; Waller, Richard; Whiteman, Colin; Kuzmina, Svetlana
Abstract: The Kidluit Formation (Fm) is a fluvial sand deposit that extends regionally across the Tuktoyaktuk Coastlands, western Arctic Canada. It was deposited by a large river flowing north into the Arctic Ocean before development of a cold‐climate sandy desert and later glaciation by the Laurentide Ice Sheet. Lithostratigraphic and sedimentological field observations of the Summer Island area indicate deposition of the Kidluit Fm by a braided river system. Optically stimulated luminescence (OSL) dating of Kidluit sand provides eight OSL ages of 76–27 ka, which indicate deposition during Marine Isotope Stage (MIS) 4 and MIS 3. Radiocarbon dating of well‐preserved weevil remains, a willow twig, wild raspberry seeds and bulrush achenes provides non‐finite 14 C ages of >52 200, >51 700, >45 900 and >54 700 14 C BP and are assigned an age of either MIS 4 or early MIS 3. Plant macrofossils from the sand deposit indicate spruce forest conditions and climate slightly warmer than present, whereas insect fossils indicate tundra conditions slightly colder than present. The river system that deposited the Kidluit Fm was probably either a pre‐Laurentide Mackenzie River or the palaeo‐Porcupine River, or a combination of the two. Copyright © 2017 John Wiley & Sons, Ltd.